Aplicação da simulação Monte Carlo na avaliação de indicadores industriais em um contexto sob incerteza - Pereira, Marina de Souza [UNESP] (2018)
The industrial environment has been developing and growing more and more bringing with it several impacts to the environment. In the last decades, environmental concerns have been gradually increasing and, as a result, companies starts to control their impacts on nature through Key Performance Indicators (KPIs). The present research aims to analyze these KPIs in a context under uncertainty using the modeling and simulation method, Monte Carlo Simulation (SMC). The materials used in this study were Microsoft Office Excel® software and Crystal Ball®. The topics presented in the theoretical basis are: KPI, indicators of sustainable development, Modeling and Simulation and SMC. The company that was chosen is a multinational consumer goods industry. It was chosen based on the great representativeness of it in the market, feasibility and facility of access the data collected during seven years. The work in question aims to analyze the applicability of SMC in the analysis of indicators in a context under uncertainty. As a result of the research it was evidenced that the KPIs could be simulated using the Crystal Ball® and that their results can helps in the decision making of the company